Analisis Rasio Likuiditas Dan Solvabilitas Pada Alfamart Dan Indomaret - Fani Mariska; Wulandari; Aris Munandar (Jurnal Manajemen Informatika & Teknologi, 2025)
Financial performance reflects a company's position compared to other companies in the same industry, which is measured through annual returns by assessing a company's performance based on its financial statements. The purpose of this study is to determine and analyze the significant differences in the Current Ratio and Debt to Equity Ratio trends between Alfamart and Indomaret. This type of research is comparative by using a table list of ratio components as a research instrument. The population in this study is all Alfamart financial statements from 1989 to 2025, which is 36 years, and Indomaret since being listed on the IDX from 1988 to 2025, which is 37 years. The sample in this study is the financial statements of Alfamart and Indomaret for 5 years, namely from 2019 to 2023. The sampling technique used in this study is purposive sampling. Data collection techniques use documentation and literature studies, then data analysis techniques use descriptive tests, normality tests, and different tests. The results of the study show that there is a difference between Debt to equity at Alfamart and Indomaret while the Current Ratio does not have a significant difference.